Safety and efficacy of an oral CCR3 antagonist in patients with asthma and eosinophilic bronchitis: a randomized, placebo‐controlled clinical trial. Issue 4 (April 2014) - Neighbour, H.; Boulet, L.‐P.; Lemiere, C.; Sehmi, R.; Leigh, R.; Sousa, A. R.; Martin, J.; Dallow, N.; Gilbert, J.; Allen, A.; Hall, D.; Nair, P.
Summary Background Several chemokines, notably eotaxin, mediate the recruitment of eosinophils into tissues via the CCR3 receptor. Objective In this study, we investigated the role of CCR3 agonists in asthma by observing the effect of a small molecule antagonist of the CCR3 receptor (GW766994) on sputum eosinophil counts in patients with eosinophilic asthma. Methods Clinical and physiological outcomes, the chemotactic activity of sputum supernatant for eosinophils and the presence of eosinophil progenitors in sputum and blood samples were also studied. Results In a double‐blind parallel group study, 60 patients with asthma were randomized to 300 mg of GW766994 twice daily or matching placebo for 10 days followed by prednisone 30 mg for 5 days. Of these patients, 53 had a sputum eosinophil count > 4.9% at baseline. Despite plasma concentrations of drug consistent with > 90% receptor occupancy during the dosing period, the CCR3 antagonist did not significantly reduce eosinophils or eosinophil progenitor cells (CD34+ 45+ IL‐5Rα+) in sputum or in blood. The ex vivo chemotactic effect of sputum supernatants on eosinophils was attenuated by GW766944 compared to placebo. There was no improvement in FEV1; however, there was a modest but statistically significant improvement in PC20 methacholine (0.66 doubling dose) and ACQ scores, (0.43). Whilst the improvement in PC20 is statistically significant, it is not of clinical significance. Conclusions and Clinical Relevance In conclusion, this study calls into question the role of CCR3 in airway eosinophilia in asthma and suggests that other cellular mechanisms mediated by the CCR3 receptor may contribute to airway hyperresponsiveness.